2018
DOI: 10.1002/ana.25341
|View full text |Cite
|
Sign up to set email alerts
|

β2‐adrenoreceptor medications and risk of Parkinson disease

Abstract: β2-adrenoreceptor agonists and antagonists do not appear to alter PD risk. Ann Neurol 2018;84:691-701.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…This case‐nested study in a large population of adults without PD followed for over 13 years showed that use of propranolol appears to be associated with an increased risk of PD, whereas use of β2‐agonists is associated with a decreased risk of PD. These data confirm a recent observation in the Norwegian population, but is in apparent contrast with the results published by Searles Nielsen and colleagues, which demonstrated no change in the risk of PD with beta adrenergic agonist or antagonists after adjusting for medication exposure lagging, demographics, smoking, and overall use of medical care.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This case‐nested study in a large population of adults without PD followed for over 13 years showed that use of propranolol appears to be associated with an increased risk of PD, whereas use of β2‐agonists is associated with a decreased risk of PD. These data confirm a recent observation in the Norwegian population, but is in apparent contrast with the results published by Searles Nielsen and colleagues, which demonstrated no change in the risk of PD with beta adrenergic agonist or antagonists after adjusting for medication exposure lagging, demographics, smoking, and overall use of medical care.…”
supporting
confidence: 84%
“…An intriguing common finding of two of these studies is that the treatment with carvedilol, a compound with alpha and beta adrenergic blocker activity not routinely prescribed for tremor, is consistently associated with a low PD risk, as evidenced by odds ratio (OR) 0.77 (95% confidence interval [CI] = 0.73–0.81) and 0.86 (95% CI = 0.73–1.02), in line with those associated with beta adrenergic agonists . Such an effect on the risk of PD appears to be dose dependent, with carvedilol doses exceeding 25 mg/day conferring a significant protective effect compared to doses of <12.5 mg/day (OR, 0.76; 95%CI = 0.67–0.86; P < 0.001) …”
mentioning
confidence: 90%
“…further report that salbutamol lowers risk of PD incidence in a large-scale epidemiological analysis of a Norwegian population whilst propranolol, a non-selective β-adrenergic receptor antagonist, increases risk (hence it being withdrawn from further investigation in the present study). Similar benefits and risks of salbutamol and propranolol have been recently supported by some 27 , but not other 28 independent reports. Although we too suggest salbutamol as a potential protective therapy for PD, we have identified a distinct mechanism, that of increased endogenous FGF20 transcription within PD-relevant tissues.…”
Section: Discussionmentioning
confidence: 62%
“…A fascinating epidemological study in Norway regarding the long-term use of β2-adrenoreceptor agonists and antagonists leading to reduced and increased risk of PD, respectively, also experimentally demonstrated that β2 receptors regulate AS transcription [38]. These findings led to hope for repurposing β2-adrenoreceptor agonists as potential disease-modifying treatment of PD, however, more recent epidemiological studies have failed to demonstrate these correlations and consider the relative protection with β2-adrenoreceptor agonists to be an indirect effect of smoking (an established reduced risk factor for PD) and the higher risk with β2-adrenoreceptor antagonists to reverse causation, i.e., PD symptoms trigger their use rather than their use triggering PD [39,40]. Thus, further studies are warranted to explore the potential for pharmacologically modulating AS expression via β2 receptors.…”
Section: As Expression Reductionmentioning
confidence: 99%